2004
DOI: 10.2190/f5vv-jpne-71at-8fuh
|View full text |Cite
|
Sign up to set email alerts
|

Gender Equity and HIV/AIDS Prevention: Comparing Gender Differences in Sexual Practice and Beliefs among Zimbabwe University Students

Abstract: We assess gender differences in HIV prevention knowledge, attitudes and practices with a focus on cultural, sociological, and economic variables. A randomized cross-sectional study was used in order to achieve high participation and broad comparative assessment. An eight-page questionnaire was administered to 933 randomly selected students at the University of Zimbabwe. Survey items addressed sexual decision-making, condom use, limiting sexual partners, cultural power dynamics and access to HIV testing. We fou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 23 publications
1
12
1
Order By: Relevance
“…The findings for gender presented above are consistent with a model of male control of sexuality that dominates the literature, particularly for southern and eastern Africa, [31][32][33][34][35][36][37][38][39] but is also discussed by Orubuloye et al 40 based on research in Nigeria. Despite variations in gender and relationship norms and power across ethnic groups and regions, the research literature consistently supports a conclusion that social, cultural, political and gender-power dynamics all constrain women's ability to introduce condoms into their relationships, [31][32][33][34][35][36][37][38][39][40] with condom use remaining predominantly under the control of men.…”
Section: Gender Influencessupporting
confidence: 84%
See 1 more Smart Citation
“…The findings for gender presented above are consistent with a model of male control of sexuality that dominates the literature, particularly for southern and eastern Africa, [31][32][33][34][35][36][37][38][39] but is also discussed by Orubuloye et al 40 based on research in Nigeria. Despite variations in gender and relationship norms and power across ethnic groups and regions, the research literature consistently supports a conclusion that social, cultural, political and gender-power dynamics all constrain women's ability to introduce condoms into their relationships, [31][32][33][34][35][36][37][38][39][40] with condom use remaining predominantly under the control of men.…”
Section: Gender Influencessupporting
confidence: 84%
“…Despite variations in gender and relationship norms and power across ethnic groups and regions, the research literature consistently supports a conclusion that social, cultural, political and gender-power dynamics all constrain women's ability to introduce condoms into their relationships, [31][32][33][34][35][36][37][38][39][40] with condom use remaining predominantly under the control of men. Improving the balance of power in heterosexual relationships through educating women has been promoted as a way to increase condom use.…”
Section: Gender Influencesmentioning
confidence: 99%
“…Young men were much more likely to use a condom compared to young women. This calls for further gender-sensitive condom promotion interventions and could be due to young women’s lower negotiation skills or self-perceived risk of HIV compared to men [ 38 , 39 ]. Moreover, around one-fifth of participants reported having extramarital or pre-marital relationships with a significantly higher prevalence among young men.…”
Section: Discussionmentioning
confidence: 99%
“…However, in contrast, this did not confirm as many other reports have noted gender differences in HIV knowledge and awareness among adolescents. A study carried on university adolescents in Zimbabwe reported that men claimed having the right of decision in the use condoms during intercourse [27]. Another study reported that gender differences in favor of males can be directed to: poor education among females, dependency on men and other socio-cultural barrier, all of which contribute to the slope knowledge of HIV/AIDS among young women [28].…”
Section: Discussionmentioning
confidence: 99%